Post-War Reconstruction - TUC report, 1945 (page 1) (1945)
1945 1939-1945 "Post-War Reconstruction - TUC report, 1945 (page 1)" [T0171.jpg], 1945, Trades Union Congress These TUC plans for economic reconstruction after the war cover public ownership or nationalisation, workers' participation, industrial democracy and price control. The report also includes the TUC's evidence to the inquiry by William Beveridge into full employment.